Chronic fatigue and associated factors among long-term survivors of cancers in young adulthood. (4th May 2019) - Bøhn, Synne-Kristin H.; Thorsen, Lene; Kiserud, Cecilie E.; Fosså, Sophie D.; Lie, Hanne C.; Loge, Jon H.; Wisløff, Torbjørn; Haugnes, Hege S.; Reinertsen, Kristin V.
Abstract: Background: Chronic fatigue (CF) is scarcely explored among young adult cancer survivors (YACSs), and more knowledge is needed to develop targeted interventions for YACSs with CF. The present study aimed to investigate the prevalence of CF and associated factors in YACSs. Also, the change of fatigue with time was explored. Material and methods: The present cross-sectional study is part of a nation-wide population based survey of Norwegian survivors of cancer in childhood, adolescence, and young adulthood (The NOR-CAYACS study).YACSs diagnosed at the age of 19–39 years with breast cancer stage ≤ III (BC), colorectal cancer (CRC), non-Hodgkin lymphoma (NHL), acute lymphoblastic leukemia, or non-metastatic malignant melanoma (MM) were included 5–30 years after diagnosis. Survivors of MM treated with limited surgery were included as a reference group. CF was assessed by the Fatigue Questionnaire. Logistic regression analyses were performed to identify factors associated with CF. Results: In total, 1488 survivors completed the questionnaire (a response rate of 42%), of which 1088 were eligible for the present study. Overall, 25% reported CF. CF was significantly more prevalent among survivors of BC (29%) ( p < .001), CRC (29%) ( p = .001) and NHL (27%) ( p = .003) than among survivors of MM (15%). CF was associated with systemic treatment combined with surgery and/or radiotherapy ( p = .018), comorbidity ( p = .038), pain ( p = .002), numbness in hands/feet ( p = .046), and depressive symptoms ( p < .001) in the multivariable model. Among survivors with CF, 60% reported that they had been tired since cancer treatment, and among these, 65% reported worsening or no change of fatigue with time. Conclusion: One of four YACSs reported CF 15 years from diagnosis (mean). CF was associated with several possibly treatable factors. Health professionals involved in the follow-up of YACSs should have knowledge of CF and approaches to manage it.